Desain Sistem Informasi Persediaan Barang di Balai Latihan Kerja, Kota Salatiga dengan Framework Bootstrap - Agustina, Nadila; Maria, Evi; Rudianto, Christ (Building of Informatics, Technology and Science (BITS), 2021)
The purpose of this research is to design an inventory information system at the Work Training Hall, Salatiga City. This research focuses on designing the system of starting the process of filing and approval of budgets, transactions of goods in and out, and recording and reporting of goods. The development of information systems in this research uses prototype methods with bootstrap framework and MySQL database. The result of this research is the design of the inventory information system to be implemented at the Work Training Hall, Salatiga City. The results showed that the design of the inventory information system produced by this research can produce accurate and timely inventory reports and free from errors. The results of the research are expected to be a solution to the problem of managing goods related to the accuracy and timely presentation of inventory reports there.